Caribbean Report 26-01-1998 - Thomas, Moya (anchor); Naysmith, Electra (correspondent); Brandt, David (interviewee); Russell, Tom (interviewee); Barnett, Carla (interviewee); Orr, Carol (correspondent); Hylton, Anthony (interviewee); Francis, Patricia (interviewee); Gibb, Tom (correspondent); Thiessen, Marc (interviewee); Collymore, Yvette (correspondent); Gordon, Orin (correspondent); et al. (The British Broadcasting Corporation, 1998)
The British government remains tight-lipped on whether it will grant full British citizenship to its dependent territories. Montserrat's Chief Minister David Brandt states that there was consensus among the Caribbean dependent territories on the issue of British citizenship. In Guyana, the list of auditors proposed by CARICOM has still not been finalized. However, Deputy Secretary-General of CARICOM, Dr. Carla Barnett comments on the delay of this process. A major CARICOM investment mission to South Africa has been joined by a trade mission from Jamaica. In Cuba, the lasting legacy of the visit of Pope John Paul II is discussed. The world looks on with high hopes that the media coverage of a more open Cuba will lead to a relaxation of US policy towards Cuba. However, Marc Theissen, the spokesman of US Senator Jesse Helms, states that no such slacking is in order. Meanwhile, a sex scandal in Washington has shifted attention as President Bill Clinton has emphatically denied that he ever had sexual relations with White House volunteer Monica Lewinsky. Rickey Singh comments on whether marital infidelity can end political careers in the Caribbean.
1. Headlines with Moya Thomas (00:00-00:23)
2. The British government remains tight-lipped on the issue of citizenship for its dependent territories (00:24-02:39)
3. The CARICOM audit team for Guyana's elections still to be finalized (02:40-04:45)
4. The lasting legacy of Pope John Paul II's visit to Cuba (07:15-09:10)
Keywords: Citizenship -- Great Britain; Great Britain -- Colonies -- Administration; Conflict management -- Guyana; Political stability -- Guyana; Trade missions; Foreign trade promotion -- Jamaica; Jamaica -- Commercial policy; Caribbean Area -- Foreign relations -- South Africa; South Africa -- Foreign relations -- Caribbean Area; Freedom of religion -- Cuba; Church and state -- Cuba; Religion and politics -- Cuba; United States -- Foreign relations -- Cuba; Cuba -- Foreign relations -- United States; Embargo; Sex scandals -- United States; Presidents -- United States; Politicians -- Sexual behavior -- United States; Mass media -- Political aspects; Sexual ethics -- Caribbean Area; Press and politics; United States. President (1993-2001 : Clinton); Clinton, Bill, 1946-; Lewinsky, Monica S. (Monica Samille), 1973-; Caribbean Community